The summer hideaway - Wiggs, Susan (Don Mills, Ont. : MIRA, 2010)
Claire Turner is a nurse with a terrible secret in her past. George Bellamy is a sick old man trying to make up for past mistakes. George's grandson Ross is a man back from a war and wanting a future. When George's illness draws Claire and Ross together, will they dare to risk everything for love?
Keywords: Nurses -- Fiction; Witnesses -- Fiction; Families -- Fiction; Man-woman relationships -- Fiction; Love stories